2017
DOI: 10.18632/oncotarget.21494
|View full text |Cite
|
Sign up to set email alerts
|

Forensic efficiency and genetic variation of 30 InDels in Vietnamese and Nigerian populations

Abstract: Insertion/deletion polymorphisms (InDels) are ubiquitous diallelic genetic markers that have drawn increasing attention from forensic researchers. Here, we investigated 30 InDel loci in Vietnamese and Nigerian populations and evaluated their usefulness in forensic genetics. The polymorphic information content of these populations ranged, respectively, from 0.164 to 0.375 and from 0.090 to 0.375 across loci. After Bonferroni correction, no significant deviation from Hardy-Weinberg equilibrium was found, except … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…The genetic distances (D A distance) were calculated among Yao, Kelao, and Zhuang samples, and the 20 referenced groups included Beijing Han (Wei et al, 2014), Guangdong Han ( Li et al, 2013), Shanghai Han (Wang et al, 2014), Yi (Liang et al, 2013), Bai (Yang et al, 2017), Xibe (Meng et al, 2015), South Korean (Seong et al, 2014), Tibet Tibetan (Wei et al, 2014), Qinghai Tibetan (Wei et al, 2014), She (Martin et al, 2013), Kazak (Wei et al, 2014), Uigur (Wei et al, 2014), Danes (Friis et al, 2012), Hungarian (Kis et al, 2012), Basque (Martin et al, 2013), Central Spanish (Martin et al, 2013), Uruguaya (Saiz et al, 2014), Jalisco Mexican (Martinez-Cortes et al, 2016), Nigeria (Du et al, 2017), Vietnamese (Du et al, 2017). The result of D A distances was illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The genetic distances (D A distance) were calculated among Yao, Kelao, and Zhuang samples, and the 20 referenced groups included Beijing Han (Wei et al, 2014), Guangdong Han ( Li et al, 2013), Shanghai Han (Wang et al, 2014), Yi (Liang et al, 2013), Bai (Yang et al, 2017), Xibe (Meng et al, 2015), South Korean (Seong et al, 2014), Tibet Tibetan (Wei et al, 2014), Qinghai Tibetan (Wei et al, 2014), She (Martin et al, 2013), Kazak (Wei et al, 2014), Uigur (Wei et al, 2014), Danes (Friis et al, 2012), Hungarian (Kis et al, 2012), Basque (Martin et al, 2013), Central Spanish (Martin et al, 2013), Uruguaya (Saiz et al, 2014), Jalisco Mexican (Martinez-Cortes et al, 2016), Nigeria (Du et al, 2017), Vietnamese (Du et al, 2017). The result of D A distances was illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To comprehensively explore the patterns of genetic affinity between our studied populations and worldwide reference populations, we merged our newly obtained population data with those of 61 worldwide populations. The final database used in the population comparison study included 6483 East Asian individuals from 38 populations [4,5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], 494 South Asians from three populations [27][28][29], 300 Vietnamese of Southeast Asia [30], 194 West Asians from two populations [31], 621 African individuals from five populations [27,30,32], 984 European individuals from eight populations [4,[31][32][33][34][35] and 1 071 South Americans from eight populations [36,38]. The detailed geographical regions and population sizes of these included populations are submitted in Supplementary Table S1.…”
Section: Reference Databasementioning
confidence: 99%
“…Development validation of the kit revealed that it was reproducible and precise and could be viewed as a stand‐alone tool for individual identifications [6]. Recently, a large number of population data in different continental populations have been reported for these 30 DIPs loci [7–12]. In previous studies, some scholars performed population genetic analyses of different continental populations based on these 30 DIP loci, and they found that some loci showed relatively high genetic divergences and might be used as candidate ancestry informative markers for ancestry analysis [8, 1315].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, previously reported population data of 30 DIPs in different continental populations [8, 9, 11, 12, 14, 15, 19–28] were gathered and analyzed to solve the three issues. First, we explored whether some DIP loci, like HLD125, HLD99, and HLD118, identified in previous studies [14, 23] were suitable for ancestry analyses of different continental populations.…”
Section: Introductionmentioning
confidence: 99%